1973
DOI: 10.1084/jem.137.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Purified Protein Derivative of Tuberculin Induces Immunoglobulin Production in Normal Mouse Spleen Cells

Abstract: Two major events occur in the response of the immune system to antigenic stimulation, proliferation of cells and secretion of soluble products. The relative importance of these two events is not well known. Mitogens have been found to provide valuable tools for analysis of these problems (for review, see reference 1). The substances most well studied are phytohemagglutinin (PHA) 1 and concanavalin A, which have been found to selectively activate thymus-derived (T) cells (2-6), and lipopolysaccharides of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
1

Year Published

1973
1973
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 18 publications
2
47
1
Order By: Relevance
“…3). It seems possible that B cells specific for DNPdeterminant are stimulated directly with DNP-PPD in the absence of Tbc-primed cells since PPD itself reveals a mitogenic activity on B cells, thus acting as a polyclonal activator for the B cells (19,22). However, this was not the case in the present study since DNP-specific B cells in DNP-OVA-primed cells were not stimulated directly with DNP-PPD without Tbc-primed cells as shown in Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…3). It seems possible that B cells specific for DNPdeterminant are stimulated directly with DNP-PPD in the absence of Tbc-primed cells since PPD itself reveals a mitogenic activity on B cells, thus acting as a polyclonal activator for the B cells (19,22). However, this was not the case in the present study since DNP-specific B cells in DNP-OVA-primed cells were not stimulated directly with DNP-PPD without Tbc-primed cells as shown in Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…For polyclonal activation spleen cell cultures were prepared at cell concentrations of 10 x 10 ~ ml. 1 ml of the suspension was incubated in 35 mm plastic Petri dishes at 37°C in an atmosphere of 83% N2, 10% CO2, and 7% O~ with or without stimulants for a period of 48 h as previously described (19). Antibody-forming cells were enumerated by a modified hemolytic plaque assay (19) using trinitrophenyl (TNP)-conjugated sheep erythrocytes (SRBC).…”
mentioning
confidence: 99%
“…In this case, the maximum response occurred on days 3-4 compared to a maximum response on day 4 when normal spleen cells were cultured with TNP-HRBC [6]. The anti-TNP response observed on day 2 was relatively insensitive to 6-MP (i.e., [6,8,9,17]. Early appearance of APC after injection of the agents mentioned above suggested that APC arose from intermediate ~ late precursor cell types.…”
mentioning
confidence: 81%